Predictive Factors for Complex Versus Simple Febrile Convulsion In Children - Mahmood, Najdat Shukur (Diyala Journal of Medicine, 2018)
Background: Febrile seizure has a good prognosis, but may presented with status epilepticus and may raise the possibility of acquiring epilepsy later in life. These consequences are highly related to many features, including complex criteria. Objective: To investigate for factors which may be associated with increased incidence of complex febrile seizure. Patients and Methods: This is a cross-sectional comparative study done within 2013- 2014. The associations of febrile convulsion and its criteria with demographic and other characters of the patients were evaluated. Chi square was applied for statistical analysis. Results: Seventy six children were enrolled, male gender was 56.6% (n=43) and 39 (51.3%) of them were having complex febrile convulsion. There was no significant effect of age and sex on the type of febrile seizure; criteria of complex febrile seizure (prolonged, repetitive, and focal seizures) were unrelated among each other. Consanguinity marriage has a clear relationship with simple type (p value=.008), vaginal delivery was significantly associated with complex seizure (p value=0.047), non- respiratory causes of fever are associated with prolonged febrile seizure (p value= .024), while no differences between the types of febrile seizur regarding many other criteria, including anemia, body weight variations, previous febrile seizure, family history of febrile seizure, and others. Conclusion: There were only a few criteria predispose the child for complex febrile seizure, including non- respiratory causes of fever, vaginal delivery, non-consanguineous parents, and possibly prematurity; therefore complex febrile convulsion cannot be entirely predicted, but a trend can be expected if these mentioned factors were experienced.